Strategi Kepala Sekolah Dalam Meningkatkan Kompetensi Profesional Tenaga Kependidikan Di SMP IT Mutiara Hati Rimbo Bujang - Rima Wira Tama; Try Susanti; Alfina Fristya Safitri; Muhammad Roihan (Indonesian Journal of Islamic Educational Management, 2025)
This study examines the Principal's Strategy in Improving the Professional Competence of Educational Personnel at SMP IT Mutiara Hati Rimbo Bujang. The formulation of the problem in this study is to find out: How is the Professionalism of Educational Personnel at SMP IT Mutiara Hati Rimbo Bujang, How is the Principal's Strategy in Improving the Professionalism of Educational Personnel at SMP IT Mutiara Hati Rimbo Bujang, and What are the Principal's Obstacles in Improving the Professionalism of Educational Personnel at SMP IT Mutiara Hati Rimbo Bujang. This study was conducted using a qualitative method with a descriptive approach. The subjects of this study were the principal, head of administration, vice principal of curriculum and administrative staff. The object of this study is the principal's efforts in improving the professionalism of educational personnel at SMP IT Mutiara Hati Rimbo Bujang. In data collection techniques, researchers used observation, interview and documentation techniques. Then this study researchers used data analysis with data reduction, data presentation and drawing conclusions. The technique of checking the validity of the researcher's data used data triangulation techniques. In this study, the author found that a strategy was needed for the principal to improve the professionalism of administrative staff, namely by conducting training, meetings, seminars, discussions and so on, and there were obstacles for the principal in improving the professionalism of administrative staff, namely inadequate human resources and inadequate facilities and infrastructure.